Physical demands associated with right-angle direct-current power-tools: An evaluation of current technology. (May 2021) - Steingraber, C.; Devries, D.; Eaton, L.; Smets, M.; Stephens, A.; Malone, G.; Porto, R.; Cort, J.
Abstract : The purpose of this work was to evaluate the physical demands associated with three direct current powered right-angle power tool tightening strategies at various fastener-location-orientations, target torques and joint-hardness. Physical demands were measured using surface electromyography, handle force and upper body kinematics. Results identified TurboTight®, a rapid and short duration fastening strategy, to produce lower handle force impulse, less joint angle displacement, and lower EMG magnitudes when compared to the longer duration fastening strategies tested. The reduced magnitudes associated with TurboTight®, independent of fastener-location-orientations, target torques and joint-hardness, indicate a lower physical demand on power tool operators, providing a significant ergonomic benefit when compared to the slower fastening strategies. Highlights: Musculoskeletal injuries are commonly associated with power-tool operation. Full programable direct-current electrically powered right-angle power tools are the standard. Physical demand comparison between the programmable tightening strategies is warranted. TurboTight® strategy was proven to have the greatest reduction in reaction force.